ANALYSIS OF THE MORPHOSTRUCTURAL CONNECTIONS BETWEEN THE EARTH CRUST CRYSTALLINE FUNDAMENT AND SEDIMENTARY LAYER OF ARMENIAN VOLCANIC HIGHLAND (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
In the paper an attempt was made to separate the morphostructure of the Earth Crust sedimentary layer and by comparative analysis with the crystalline fundament's surface to explore the existing morphostructural connections between these layers on the territory of Armenian volcanic highland.
Keywords: Armenian volcanic highland; Earth Crust crystalline fundament; Earth Crust sedimentary layer; morphostructural connections